The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1063/1.3646918
|View full text |Cite
|
Sign up to set email alerts
|

A study of dust grain screening in a weakly ionized plasma based on the numerical solution of the Vlasov-Bhatnagar-Gross-Krook kinetic equations

Abstract: Screening of a dust grain in a weakly ionized plasma is studied for a wide range of collisional regimes. The problem is considered on the basis of the Vlasov-Bhatnagar-Gross-Krook equations for plasma particles. The equations are solved numerically on parallel processors by means of a high-order finite-volume method. The computations are carried out for different pressures of plasma background and different grain sizes. The values of the total grain charge, distributions of the electric potential, and basic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…This is particularly relevant in complex plasmas, where continuous absorption of plasma electrons and ions on the particle surface result in inverse-power-law asymptotes of interaction at large interparticle separations. 5,[8][9][10][11] Plasma production and loss processes can also produce a double-Yukawa interaction potential characterized by two different screening lengths. 12,13 Nevertheless, many experimentally observed trends can be already reproduced by the simplest model considering point-like particles interacting via the repulsive Yukawa potential (1), at least qualitatively.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly relevant in complex plasmas, where continuous absorption of plasma electrons and ions on the particle surface result in inverse-power-law asymptotes of interaction at large interparticle separations. 5,[8][9][10][11] Plasma production and loss processes can also produce a double-Yukawa interaction potential characterized by two different screening lengths. 12,13 Nevertheless, many experimentally observed trends can be already reproduced by the simplest model considering point-like particles interacting via the repulsive Yukawa potential (1), at least qualitatively.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the neutralizing medium on the effective interactions between the particles can involve more than only screening. This is particularly relevant in complex plasmas, where continuous absorption of plasma electrons and ions on the particle surface (for simplicity we neglect the electron emission processes, which can play a role in certain situations, and then can make the problem even more complicated) results in inverse-power-law asymptotes of interaction at large interparticle separations [2][3][4][5][6][7][8]. At intermediate distances deviations from the simple form (1) can be expected when ion-particle interaction is highly non-linear [9][10][11] or a significant fraction of trapped ions is present [12].…”
Section: Introductionmentioning
confidence: 99%
“…[38,39] The ion-neutral collisions were shown to affect the far-field behaviour of the potential around an absorbing particle in the isotropic case. [28,29,36] The studies based on a linear kinetic model showed that the asymptotic behaviour of the potential is determined by the Coulomb-like term (i.e., 𝜑 ∼ r −1 ) in the weakly and highly collisional regimes. This result was confirmed by the numerical simulations based on the direct solution of the model kinetic equations.…”
Section: Screening Of Dust Particlesmentioning
confidence: 99%
“…Self-consistent numerical simulations of dust particle charging in collisional plasma were performed by Zobnin, [25] Lampe, [26] Hutchinson and Patacchini, [27] and Semenov. [28,29] The simulations of Zobnin, Hutchinson, and Patacchini were based on the particle-in-cell approach combined with the Monte-Carlo collisions model, whereas Lampe used a semi-analytical model based on integral expressions for the ion current near the particle. The simulations of Semenov were based on the direct numerical solution of kinetic equations for plasma components using model collision integrals.…”
Section: Particle Chargingmentioning
confidence: 99%